2022
DOI: 10.5670/oceanog.2022.103
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Mixing in a Changing Arctic Ocean

Abstract: Historically, the Arctic Ocean has been considered an ocean of low variability and weak turbulent mixing. However, the decline in seasonal sea ice cover over the past couple of decades has led to increased coupling between the atmosphere and the ocean, with potential enhancement of turbulent mixing. Here, we review studies that allow identifying energy sources and pathways that lead to turbulent mixing in an increasingly ice-free Arctic Ocean. We find that the evolution of wind-generated, near-inertial oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…It was also found that only about 20% of the increased Atlantic Water concentration above the 34.8 isohaline in the Eurasian Basin can be attributed to the Fram Strait branch (Wang et al, 2019b). Therefore, although sea ice decline can increase vertical mixing (e.g., Rainville and Woodgate, 2009;Polyakov et al, 2020b;Rippeth and Fine, 2022), thus increasing halocline salinity through mixing saline Atlantic Water upwards, this process is not the major contribution to the salinification of the halocline in the Eurasian Basin. In addition, the positive salinity anomaly in the Barents Sea induced by sea ice decline could contribute to the positive salinity anomaly in the eastern Eurasian Basin too, but the larger salinity anomaly associated with sea ice decline in the eastern Eurasian Basin than in the upstream Barents Sea implies that this contribution is small (Figure 12F).…”
Section: Impact Of Sea Ice Decline On Arctic Atlantificationmentioning
confidence: 99%
“…It was also found that only about 20% of the increased Atlantic Water concentration above the 34.8 isohaline in the Eurasian Basin can be attributed to the Fram Strait branch (Wang et al, 2019b). Therefore, although sea ice decline can increase vertical mixing (e.g., Rainville and Woodgate, 2009;Polyakov et al, 2020b;Rippeth and Fine, 2022), thus increasing halocline salinity through mixing saline Atlantic Water upwards, this process is not the major contribution to the salinification of the halocline in the Eurasian Basin. In addition, the positive salinity anomaly in the Barents Sea induced by sea ice decline could contribute to the positive salinity anomaly in the eastern Eurasian Basin too, but the larger salinity anomaly associated with sea ice decline in the eastern Eurasian Basin than in the upstream Barents Sea implies that this contribution is small (Figure 12F).…”
Section: Impact Of Sea Ice Decline On Arctic Atlantificationmentioning
confidence: 99%
“…The highly intermittent nature of turbulence requires both long sampling periods to obtain representative average values, and a high sampling frequency to capture short-term variability in response to environmental forcing. Especially in the rapidly changing Arctic, repeated sampling campaigns are necessary to assess the response of turbulent transport to climate change, as vertical mixing in the Arctic Ocean is expected to increase in response to trends in the environmental conditions, with implications for the future maintenance of sea ice and Arctic Ocean primary production (e.g., Rippeth & Fine, 2022). The method comparison presented in this paper was initiated by Dr. David Kadko.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…The high‐frequency variability is beyond the scope of this study. Peterson (2017) and Wang et al. (2022), have described the near‐inertial and the tidal variability, respectively, using the data from the moorings used here.…”
Section: Observationsmentioning
confidence: 99%